1984
DOI: 10.1113/expphysiol.1984.sp002795
|View full text |Cite
|
Sign up to set email alerts
|

Renal Control of Plasma Urea Level in Sheep: The Diuretic Effect of Urea, Potassium and Sodium Chloride

Abstract: Two merino ewes were fed 800 and then 1000 g of lucerne chaff per day and renal responses and extracellular fluid volume (E.C.F.) were determined. Urine urea nitrogen, glomerular filtration rate (G.F.R.), urine volume, effective renal plasma flow (E.R.P.F.) and E.C.F. increased in both animals with the greater nitrogen intake. In a second experiment, five merino wethers and four merino ewes were infused intraruminally with increasing quantities of urea, whilst being fed a mainly roughage ration, and the above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The secretion of saliva increases during mastication, especially when the animal is ruminating (Church, 1979 Renal urea excretion is reported to be positively correlated with urine flow rate in sheep (Cocimano and Leng, 1967;Godwin and Williams, 1984 (Nolan and Leng, 1970) and in pregnant and lactating Merino sheep (Oddy et al, 1983). The high potential for nitrogen conservation during the two productive states could be of special importance for breeds such as the Sardi, which usually graze vegetation poor in nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of saliva increases during mastication, especially when the animal is ruminating (Church, 1979 Renal urea excretion is reported to be positively correlated with urine flow rate in sheep (Cocimano and Leng, 1967;Godwin and Williams, 1984 (Nolan and Leng, 1970) and in pregnant and lactating Merino sheep (Oddy et al, 1983). The high potential for nitrogen conservation during the two productive states could be of special importance for breeds such as the Sardi, which usually graze vegetation poor in nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…This is a typical effect of increased NaCl intake (Dirks et al 1976;Godwin & Williams, 1984). Potter (1961) found that sheep given 13 g NaC1/1 as drinking water, through which they voluntarily consumed 1000 mmol NaCl/d for prolonged periods, have a n increased GFR and a reduced ERPF resulting in a greater renal filtration fraction.…”
Section: Discussionmentioning
confidence: 99%
“…However the salt intake from this treatment was only about 20 mmol/kg body-weight per d. In the present study this level, equivalent to about 750 mmol/d, had little effect on the indices of N metabolism measured. Previous work from this laboratory has shown that relatively small intraruminal infusions of NaCl (500 mmol/d) will reduce the high plasma urea concentrations of urea-loaded sheep by increasing the renal excretion of urea (Godwin & Williams, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations